Cognitive inter-ventions combined with tDCS for adolescents with neurodevelopmental disorders – focus on aggressive behaviour. Literature review - Pavlou Papagianni, Liza; Kambanaros, Maria (My University, 2018)
When designing interventions for adolescent students presenting neurodevelopmental disorders we usually face the problem of aggressiveness. A behaviour that most frequent co-exist with elevated risk of school dropout for these students. Experience in the field shows that: there is a need for comprehensive assessment of domain general cognitive functions such as attention, memory and executive functions as well as language abilities in adolescence with neurodevelopmental disorders and aggression. Deficits in these areas are thought to account for functional impairments that adolescents with neurodevelopmental disorders display across a range of settings including academic difficulties, behavioural problems and social isolation. Additionally, an intervention protocol for specific cognitive tasks (cognitive training), with the goal of increasing the underlying executive functions (including memory and attention) should be designed and implemented. Finally, in order to augment outcomes, technology such as tDCS should be used in combination with cognitive training / interventions. To come up with a novel intervention protocol, we conducted a literature review, among articles published from 01/2000 to 08/2018. First we searched for (cognitive) interventions provided for adolescents diagnosed with a neurodevelopmental disorder. The second theme was how is the technology of transcranial direct stimulation, utilised in the field of interventions for neurodevelopmental disorders? Finally is there a common ground where conventional cognitive interventions meet with tDCS? And if yes, what are the outcomes? Is this a fruitful combination? Is there any research evidence supporting (or rejecting) the combination of the two methodologies? This search surprisingly gave only limited number of articles discussing the combined theme of cognitive interventions targeting on aggressive behaviours in adolescence, implementing the Transcranial Direct Current Stimulation, despite the growing need for these kinds of treatments and the growing utilization of tDCS along with cognitive interventions. The poster will summarize the results or the literature review.
Keywords: Adolescent students; Aggressiveness